THE METHODOLOGICAL FOUNDATIONS FOR DEVELOPING CRITICAL THINKING SKILLS USING MODERN PEDAGOGICAL TECHNOLOGIES - Allamuratova Khurliman Nurilla qizi (Western European Studies, 2024)
This article examines the importance and application of project-based and problembased activities in modern teaching methods. It explores the similarities and differences between these approaches, emphasizing their role in encouraging active learning and developing critical thinking abilities in students.
Keywords: Project work; multi-level task; intra-class